Under Sleeper Pads in Railway Track - Otto Plasek; Miroslava Hruzikova; Richard Svoboda; Jaroslav Bilek (Communications - Scientific letters of the University of Zilina, 2014)
Under sleeper pads appear to be suitable measure to improve track quality as a consequence of ballast bed protection against extreme stress. The paper comprises experience of under sleeper pads applications in the Czech Republic in two test sections which were built in the Czech Republic in 2007. The tests sections were built with the aim to protect permanent way elements against extremely high dynamic loading. That is why all parameters which could be influenced by the application of USPs are assessed, especially track quality, deflection and vibration of sleepers and bearers. Some positive influence of under sleeper pads on the track quality was observed after six years of monitoring. Extension of the application of under sleeper pads is expected in the Czech Republic especially for switches and crossings.